Direct healthcare costs and their relationships with age at start of drug use and current pattern of use: a cross-sectional study - Becker, Paula; Razzouk, Denise (São Paulo Medical Journal, 2021)
BACKGROUND: It is well known that early start of drug use can lead users to psychosocial problems in adulthood, but its relationship with users’ direct healthcare costs has not been well established OBJECTIVES: To estimate the direct healthcare costs of drug dependency treated at a community mental health service, and to ascertain whether early start of drug use and current drug use pattern may exert influences on these costs. DESIGN AND SETTING: Retrospective cross-sectional study conducted at a community mental health service in a municipality in the state of São Paulo, Brazil. METHODS: The relationships between direct healthcare costs from the perspective of the public healthcare system, age at start of drug use and drug use pattern were investigated in a sample of 105 individuals. A gamma-distribution generalized linear model was used to identify the cost drivers of direct costs. RESULTS: The mean monthly direct healthcare costs per capita for early-start drug users in 2020 were 1,181.31 Brazilian reais (BRL) (274.72 United State dollars (USD) according to purchasing power parity (PPP)) and 1,355.78 BRL (315.29 USD PPP) for late-start users. Early start of drug use predicted greater severity of cannabis use and use of multiple drugs. The highest direct costs were due to drug dependence combined with alcohol abuse, and due to late start of drug use. CONCLUSIONS: Preventive measures should be prioritized in public policies, in terms of strengthening protective factors before an early start of drug use.